Application of yeast to understanding the mode of action of the antimalarial drug artesunate - Wilson, Jonathan M. (2014)
The aim of this project was to use the budding yeast model, Saccharomyces cerevisiae, in order to investigate the mode of action of the antimalarial drug artesunate. Using a range of techniques and resources available for S. cerevisiae, the research has identified two potential genes of interest, CDC73 and ADH1. The absence of either one of the genes causes increased sensitivity to artesunate in S. cerevisiae grown in the rich broth medium, YEPD. Such sensitivity of both deletion strains was only apparent on fermentable medium. Overexpressing both CDC73 and ADH1 in wild type backgrounds had no effect on the sensitivity of yeast to artesunate, suggesting that neither are direct targets of the drug. The increased sensitivity of the adh1Δ mutant relative to the wild type was dependent on the presence of oxygen whereas that of cdc73Δ cells appeared not to be. It was not possible within the timeframe of the project to discern why cdc73Δ yeast cells experience heightened sensitivity to artesunate, but it was established that they are able to produce ethanol and that they show higher intracellular superoxide than wild type cells. The cause of the adh1Δ mutant’s increased sensitivity to artesunate was hypothesised to be a shift in metabolism towards aerobic respiration, resulting in activation of the drug. The dependence of adh1Δ cells’ increased sensitivity to artesunate on the presence of oxygen is consistent with existing models of artemisinin damage to yeast cells that are characterised by reactive oxygen species production. Because the cdc73Δ mutant potentially remains hypersensitive to artesunate in anaerobic conditions it suggests that artesunate damage may not be mediated via reactive oxygen species, which suggests that the two genes most likely confer artesunate resistance in wild type cells by different mechanisms. This could be consistent with the possibility of at least two mechanisms by which artesunate causes growth inhibition in yeast.